Breastfeeding rates at discharge for very low birthweight neonates and their determinants: An observational study from a tertiary care neonatal intensive care unit in India. (2nd July 2022) - Chauhan, Avantika; Kumar, Mala; Tripathi, Shalini; Singh, Shakal N; Singh, Vijay K
Abstract : Background: Mother's milk is the best milk for neonates. Preterm very low birthweight (VLBW) neonates face many challenges leading to low rates of breastfeeding at discharge. Aims: (i) To determine the proportion of <32 weeks preterm VLBW neonates who are exclusively breastfed (EB) at discharge and (ii) determinants of exclusive breastfeeding (EBF) at discharge. Methods: An observational study was conducted for a duration of 1 year, from May 2019 to April 2020 in a tertiary care neonatal intensive care unit (NICU) in North India. Consecutive <32 weeks preterm VLBW neonates admitted within 72 h of birth and on full enteral feeds (FEF) within 10 days of birth were included in this study and followed up till discharge. Results: Forty‐four of 97 (45.4%) preterm VLBW neonates were exclusively breastfed and 31/97 (32%) received more than 80% mother's own milk (MOM) at discharge. Male sex ( P = 0.03), those whose first feed had any amount of MOM ( P = 0.038) or exclusive MOM in their first feed or when initiated on first FEF ( P = 0.002), and neonates with longer duration of hospital stay ( P = 0.035) had an increased chance of being exclusively breastfed at discharge. Conclusion: Preterm VLBW neonates who receive any amount of MOM in their first feed or first FEF, male infants and those who stay longer in hospital are more likely to be exclusively breastfed at discharge.